Excessive eccentric exercise-induced overtraining model leads to endoplasmic reticulum stress in mice skeletal muscles - Pereira, Bruno C.; Da Rocha, Alisson L.; Pinto, Ana P.; Pauli, José R.; De Souza, Claudio T.; Cintra, Dennys E.; Ropelle, Eduardo R.; De Freitas, Ellen C.; Zagatto, Alessandro M. [UNESP]; Da Silva, Adelino S.R. (Elsevier, 2016)
Aims The present study verified the responses of selected endoplasmic reticulum (ER) stress proteins (i.e., BiP, ATF-6, pIRE1, pPERK, and peIF2alpha) in mice skeletal muscles after three different running overtraining (OT) protocols with same external load (i.e., intensity vs. volume), but performed in downhill, uphill and without inclination. Materials and methods The rodents were randomly divided into control (CT; sedentary mice), overtrained by downhill running (OTR/down), overtrained by uphill running (OTR/up) and overtrained by running without inclination (OTR) groups. The incremental load test and exhaustive test were used as performance parameters. Forty hours after the exhaustive test performed at the end of the OT protocols (i.e., at the end of week 8) and after a 2-week total recovery period (i.e., at the end of week 10), the extensor digitorum longus (EDL) and soleus muscles were removed and used for immunoblotting. Key findings For both skeletal muscle types, the OTR/down protocol increased the pIRE-1, pPERK and peIF2alpha, which were not normalized after the total recovery period. At the end of week 8, the other two OT protocols up-regulated the BiP, pPERK and peIF2alpha levels only for the soleus muscle. These ER stress proteins were not normalized after the total recovery period for the OTR/up group. Significance The above findings suggest that the OTR/down protocol-induced skeletal muscle ER stress may be linked to a pathological condition in EDL and soleus muscles.
Keywords: ER stress; Mice; Overtraining protocols; Skeletal muscles